PROJEKT KONWENCJI NARODÓW ZJEDNOCZONYCH O SPRAWIEDLIWOŚCI ORAZ WSPARCIU DLA OFIAR PRZESTĘPSTW I NADUŻYĆ WŁADZY - Bieńkowska, Ewa (Zeszyty Prawnicze, 2016)
Draft of the UN Convention on Justice and Support for Victims of Crime and Abuse of Power Summary The paper gives an account of the provisions of the draft of the UN Convention on Justice and Support for Victims of Crime and Abuse of Power of 8 February 2010. The aim of the new UN document is to strengthen the position of victims around the world, by extending the scope of the rights granted them under the UN Declaration on Basic Principles of Justice for Victims of Crime and Abuse of Power of 29 November 1985. The description of these rights provides a basis for a discussion of the need of the Convention.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />